Efektifitas Konseling Behavioral Untuk Meningkatkan Penyesuiaan Sosial Siswa - Deni Kamali (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
Abstract : Students with behavioral barriers in social adjustment are considered capable of limiting personality formation and self-actualization throughout life, especially in terms of academic achievement. Because humans are motivated in meeting needs, social adjustment can occur. Observations made on September 17, 2021 at SMP Sabiliyah revealed that some students experienced social problems such as being aloof, apathetic, not talking much in class, which had to be overcome through counseling with a behavioral approach by the BK teacher at SMP Sabiliyah.Keyword : Social Adjustment and Behavioral Counseling